Applying nanoemulsions produced from the essential oil mixture of citronella and Coleus Amboinicus to preserve minced chicken meat - Tan Phat Vo; Nguyen Van Nhi Le; Tan Triet Tcheng; Le Song Tu Pham; Tong Minh Quan Truong; Ngoc Bao Vy Nguyen; Dinh Quan Nguyen (PLoS ONE, 2026)
This study investigated the preservative potential of four essential oils (EOs): citronella (Ci), Litsea cubeba (Lc), Coleus amboinicus (Ca), and kaffir lime (Kl) for minced chicken (MC). Their major constituents (geraniol, citral, isobornyl acetate, and D-limonene, respectively) were identified, and their antibacterial and antioxidant capacities were evaluated. A mixture of Lc and Ca displayed the lowest MIC against L. plantarum (2 µL/mL), while citronella showed the highest activity against E. coli (6 µL/mL). Synergy analysis indicated that the CiCa combination produced the strongest antibacterial response and exhibited the highest antioxidant capacity. Based on this dual bioactivity, the CiCa mixture was formulated into a nanoemulsion and incorporated into a chitosan film to develop a nanoemulsion phase inversion chitosan film (NPICF). When applied to MC and stored for 10 days, NPICF significantly delayed spoilage, maintaining a low total viable count (3.92 log 10 CFU/g) and total volatile basic nitrogen (1.59 mg/100 g), while preserving texture (hardness: 663 g; cohesiveness: 0.376). These findings demonstrate that NPICF is a promising natural strategy for extending the shelf-life and maintaining the quality of minced chicken.